Adsorption of hard sphere fluid in porous material: A Monte Carlo simulation approach for pressure calculation - Orea, P.; Duda, Yu. (Condensed Matter Physics, 2003)
We have performed Monte Carlo simulations in the canonical ensemble of a hard-sphere fluid adsorbed in microporous media. The pressure of the adsorbed fluid is calculated by using an original procedure that includes the calculations of the pressure tensor components during the simulation. In order to confirm the equivalence of bulk and adsorbed fluid pressures, we have exploited the mechanical condition of equilibrium and performed additional canonical Monte Carlo simulations in a super system “bulk fluid + adsorbed fluid”. When the configuration of a model porous media permits each of its particles to be in contact with adsorbed fluid particles, we found that these pressures are equal. Unlike the grand canonical Monte Carlo method, the proposed calculation approach can be used efficiently to obtain adsorption isotherms over a wide range of fluid densities and porosities of adsorbent.